2016
DOI: 10.1111/trf.13557
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive pH monitoring for bacterial detection in platelet concentrates

Abstract: The pH SAFE system allows for repeated, noninvasive pH screening during PC storage. A significant decrease in pH could serve as an indicator of clinically significant levels of bacterial contamination. Since differences in pH decline were observed among bacterial species, continuous pH monitoring in PCs is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Moreover, pH is used as an indicator for bacterial growth as bacteria produce by-products that are acidic, leading to a drop in pH [23]. For this reason, studies have also suggested the use of pH to monitor for bacterial contamination [24,25]. This decrease in pH over storage days is consistent with the literature available.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, pH is used as an indicator for bacterial growth as bacteria produce by-products that are acidic, leading to a drop in pH [23]. For this reason, studies have also suggested the use of pH to monitor for bacterial contamination [24,25]. This decrease in pH over storage days is consistent with the literature available.…”
Section: Discussionsupporting
confidence: 75%
“…It would be reasonable to hypothesize that the utilization of glucose by bacteria could create a microenvironment with a decreased pH that stimulates the exportation of cytoplasmic proteins to the cell surface to form a proteinaceous biofilm matrix. Indeed, a decrease in pH in contaminated PCs has been associated to high titres of bacterial contamination [48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional pH meters have been deemed inadequate because of the high ionic strength and contamination of bacterial metabolites on the electrode surface of the culture medium. As a result, a series of new pH sensors have been developed to accurately measure bacterial growth. , These methods may be classified into two categories: electrochemical methods ,, and optical detection. ,, Electrochemical methods based on redox reactions are typically susceptible to interference from the cultural solution of bacteria, as these interferences may react with the working electrodes. Furthermore, the high salt concentration of the cultural solution also affects the electrochemical reaction, resulting in a reduction in the sensitivity of the method based on field effect transistors due to the decrease of the double layer.…”
Section: Introductionmentioning
confidence: 99%